Pengaruh Perputaran Kas, Perputaran Persediaan, dan Perputaran Piutang terhadap Profitabilitas Perusahaan - Darmayanti, Ni Kadek Dewi; Yadnya, I Putu (E-Jurnal Manajemen; Vol 3 No 10 (2014), 2014)
This study underscores the influence of factors such as cash turnover, inventory turnover and accounts receivable turnover on the profitability of companies in the food and beverage sector in IDX. In the study population of 16 food and beverage companies. Samples were selected by purposive sampling method, which resulted in 13 companies as the study sample. Based on the analysis it was found that the variable cash turnover, inventory turnover and accounts receivable turnover partially and simultaneously have positive and significant impact on the profitability of food and beverage company in BEI 2010-2012. Keywords: cash turnover, inventory turnover, accounts receivable turnover, profitability
Keywords: cash turnover, inventory turnover, accounts receivable turnover, profitability